Isolated Tuberculosis of Gallbladder: A Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Tuberculosis of the gall bladder, a rarity in itself, is always found associated with gallstones or cystic duct obstruction. It presents as a part of systemic miliary tuberculosis, abdominal tuberculosis, isolated gallbladder tuberculosis and as acalculus cholecystitis in anergic patients. There are no pathognomonic signs;the diagnosis depends on suspicion of tuberculosis, preoperative findings and histological examination. This is case of a 60 year old diabetic smoker male; who presented with features of calculouscholecystitis, but after cholecystectomy, on histopathology was proved to be tuberculous gall bladder. The present case of tuberculosis of the gall bladder is being reported for its extreme rarity as it was associated gallstones and thick walled gallbladder mimicking neoplasm. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22887 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 61-63